(untitled) (Research, Society and Development, 2020)
This article presents a discussion about the profile of the student registered in the Civil Engineering Graduation course at the Instituto Federal de Minas Gerais (IFMG) – Campus Piumhi. This is a descriptive and exploratory research with a sample of 120 students, in which we used a virtual and physical questionnaire with information about social, professional and economic aspects. The results showed that most students are male (55%), they live with their parents (45%) and whose family income is between two and four minimum wages (46%), get around on foot (50.0%), their meals are made at home (72.0%), they attended high school in public school (68.0%) and they have some kind of study grant (52%). Regarding the course, the majority chose Civil Engineering course as first option (77%), and those who did not, had as their first option Architecture and Urbanism course (29,0%). The main reason for choosing the course was vocation (36.0%), and the majority chose the Institute due to its location (55.0%). Overall, the respondents intend to practice the profession in a private company (38.0%) and want to continue their studies after graduation (48.0%). The aim of this paper is to guide better the campus management, through the knowledge of the student body, generating benefits to all involved.